Assessment of Knowledge and Experience of Hunters on Natural Saltlicks of Old Oyo National Park (2020)
Background: The impetus behind wildlife geophagy has not only remained a mystery but continued to gain scientists attention lately. To this day, lucking around natural saltlicks (NSs) for hunting or poaching on geophagic animals is not uncommon among hunters, especially in a protected area. Although, hunters’ reasons for doing so may seem obvious but their experience over the years had not only suffered neglect but also lack of documentation. Perhaps, understanding this experience may help unravel the geophagic impetus. This study therefore focused on the collection of information on the existing knowledge of hunter-wildlife-saltlick relationships in Old Oyo National Park (OONP). Materials and Methods: Data were collected by interviewing 18 respondents (3 workers of OONP and 15 hunters) using purposive, snow ball and convenient sampling techniques. Information gathered from the interview was subjected to thematic content analysis and was followed up by observation method. Result: The result revealed 36 locations (including Wawa, Ajaku, Ibuya, Toka, Olotaara, Olopekan, Odo koko, Ayinta, Eleekan, Ipade aaye, Alalegba, Agbon eerin, Igbo alata, Aladere, Tofolo e.t.c) that were thought to contain numerous NSs in the park. Apart from hunters and wildlife (like giant rat, kob, waterbuck, bushbuck, duiker, baboon) which directly utilize NSs, some members of the community (especially pregnant women of certain family) also utilize the NSs indirectly. Conclusion: Hunters have verse knowledge of NSs of OONP than have been envisaged and their experience is too important to be neglected. This suggests the importance of considering knowledge of members of the community for incorporation in formulating conservation policy for protected areas.